The How Social Media and Mental Health Affect Teen Productivity and Discipline - Wulandari, Refiana Putri; Herman, Herman; Xavieranisa, Najwa; Mariam Luluatin Alambaria, Zomrotul (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
Social media has become a prominent part of daily life, particularly among university students, influencing their mental health, productivity, and discipline. This study investigates the effects of social media usage and mental health on academic productivity and discipline among students of the Faculty of Economics and Business at Pakuan University. Using a quantitative correlational design, data were collected through surveys distributed to 150 respondents aged 18–24 years. Statistical analysis was conducted using SPSS, focusing on correlation and regression tests to measure the relationships between variables. The findings reveal that social media usage negatively impacts discipline, as excessive use contributes to distraction and diminished focus on academic tasks. Mental health challenges also show a significant negative effect on both productivity and discipline, highlighting the need for students to manage stress and develop effective self-regulation strategies. This study emphasizes the importance of promoting digital literacy and mental health awareness to help students maintain a balance between their social and academic lives, ultimately improving their overall well-being and academic outcomes.